The Correlation between Learning Styles and Academic Achievement of English Education Second Semester at FKIP Batanghari University Jambi. - Kartika Dewi (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2026)
The purpose of this study is to determine whether students' learning preferences and academic success are related. The researcher used the correlation method in quantitative design. Questionnaire and student transcripts served as the data collection tools. The sample consisted of 22 students. Data questionnaire used analyzed by using Pearson Product Moment Formula. It was used to analyzing the question base on the category of students learning style. The Second Semester English Education Students’ of Batanghari University. Findings of the students' learning styles also indicate that, out of all the other kinds of learning styles, The findings indicated that the majority of students selected Visual + Kinesthetic learning styles. Additionally, the mean score of 81 indicates that the second semester English education students at FKIP Batanghari University in Jambi had an excellent learning style. The average student achievement score in learning English was 83, which is considered very high. Students' achievement and their learning style did not correlate well. R analysis was 0.750, falling between 0.60 and 0.799, indicating high correlation. between their learning style and their performance in English classes.